ROLE OF TROPICAL PLANTS IN ASTHMA MANAGEMENT (FUDMA JOURNAL OF SCIENCES, 2024)
Africa is endowed with a rich variety of plants. Most of the plants are used to treatment and manage diseases; thus, promoting good health. New plants are usually tried when observed that domestic animals feed on them without experiencing any visible discomfort.  However, the use of traditional medicine has been neglected as soon as modern medicine began to flourish. As associated side-effects of synthetic drugs are increasingly being discovered, there is a need to explore the use of plant-based therapeutics in the management of diseases like hypertension, asthma and cancer that have resulted in huge loss of human resources and economic downturn. Therefore, two hundred reports of empirical studies on the application of tropical plants in the management of asthma were collected from credible online sources, organised, studied, and analysed. The results demonstrated the plants some of the plants studied exhibited anti-asthma properties using anti-inflammatory, anti-histamine responses, and antioxidant mechanisms, respectively. Hence, tropical plants possess certain bioactive compounds with anti-asthma effects. Objectively applied, tropical plants can be used to effectively prevent and manage asthma with minimal or no side-effects.
Keywords: Anti-asthma; Asthma; Phytochemistry; Phytomedicine; Tropical plants